عہد نبوی میں محنت کشوں کی فلاح کے لیے عملی اقدمات: Practical Measures for the Welfare of workers in the Prophetic era (Al-Aasar, 2025)
The Economic development and prosperity of any nation is not possible without the continuous efforts of hardworking and talented people. Therefore, practical measures to improve their welfare and quality of life are the first priorities of Islam. Before his mission, the Messenger of Allah (S.A.W.S) considered as an honor all such measures for upholding the principles of justice and justice, through which the rights of workers could be protected. The element of simplicity and hard work was always dominant in his life. When Sayyiduna Abu Talib prepared for the trade journey, he also joined him in the hard work of the journey. He (peace be upon him) explained every aspect of the economy with practical examples and made self-effacement a slogan. This hard work was not only a temporary act to provide an example, but the entire life of the Prophet (S.A.W.S) was full of hard work. The study of Sirat al-Mutahrah provides twenty such examples of how the Prophet (S.A.W.S) worked hard for sustenance, social welfare and national pride. And also took practical measures for the welfare of the workers. In this article, the practical measures taken for the workers during the time of the Holy Prophet (PBUH) will be reviewed.